Self-Organizing Systems 5th International Workshop, IWSOS 2011, Karlsruhe, Germany, February 23-24. 2011. Proceedings - Bettstetter, Christian; Gershenson, Carlos; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 5th International Workshop on Self-Organizing Systems, IWSOS 2011, held in Karlsruhe, Germany, in February 2011. The 9 revised full papers presented together with 1 invited paper were carefully selected from 25 initial submissions. It was the 5th workshop in a series of multidisciplinary events dedicated to self-organization in networked systems with main focus on communication and computer networks. The papers address theoretical aspects of self-organization as well as applications in communication and computer networks and robot networks.
Electronic reproduction.
Keywords: Self-organizing systems -- Congresses; Computer networks -- Congresses; Electronic book